Super-Enhancement and Control of Amh Expression - Dresser, David W. (Scientific Research Publishing, 2016)
In previous work it was shown that mutation of site 1 in the downstream enhancer sequence (DE) led to ablation of enhancement. Mutation of the Wilms tumour factor element (Wt), situated in the Amh promoter between the tata box and the start of translation (TSS), also led to ablation of enhancement. This suggested that these sites may be the anchor points for a specific duplex factor bridging remote DNA elements to the promoter. Mutation analysis of the DNA sequence between sections 1 and 2 of DE was carried out by site directed mutagenesis. It is reported here that site 4 lying between DE1 and DE2, plays a key role in controlling the level of enhancement.
Keywords: Enhancement; Super-Enhancement; Amh; Gene Expression